Comparison of ontology with non-ontology tools for educational research - Roman A. Tarasenko; Viktor B. Shapovalov; Stanislav A. Usenko; Yevhenii B. Shapovalov; Iryna M. Savchenko; Yevhen Yu. Pashchenko; Adrian Paschke (Academy of Cognitive and Natural Sciences, 2021)
Providing complex digital support for scientific research is an urgent problem that requires the creation of useful tools. Cognitive IT-platform Polyhedron has used to collect both existing informational ontology-based tools, and specially designed to complement a full-stack of instruments for digital support for scientific research. Ontological tools have generated using the Polyhedron converter using data from Google sheets. Tools "Search systems", "Hypothesis test system", "Centre for collective use", "The selection of methods", "The selection of research equipment", "Sources recommended by Ministry of Education and Science of Ukraine", "Scopus sources", "The promising developments of The National Academy of Sciences of Ukraine" were created and structured in the centralized ontology. A comparison of each tool to existing classic web-based analogue provided and described.